Islamic Finance and Sustainable Development Goals (SDG): A Bibliometric Review - Aam Slamet (SMART Insight, 2020)
Islamic finance plays an important role in sustainable development. Sharia offers a comprehensive approach to many elements of life, including transactions. Sharia provides moral standards for economic operations and transactions in addition to legal laws. It outlines the fundamental ideas of economic systems, such as property rights, contacts, economic activity, and the principles that govern the behaviour and activities of individuals, markets, and the economy. Where Islamic financial instruments focus on implementing a vision that lies in three aspects: economic growth, social inclusion, and environmental protection. In this context, the goals of Islam are in line with the objectives of the sustainable development agenda (SDGs) which are to increase economic growth and realize a prosperous life and eliminate poverty. This study aims to determine the development of research trends in Islamic Finance and Sustainable Development Goals published by leading journals on Islamic financial economics. The data analyzed consisted of 79 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of the development of Islamic Finance and Sustainable Development Goals research.